2016
DOI: 10.4172/2252-5211.1000232
|View full text |Cite
|
Sign up to set email alerts
|

An Approach on Environmental Sanitation Situation and Toilets Septic Tank Design in Urban Nigeria: A Case Study of Calabar South

Abstract: In this study, the research protocol was designed for two key objectives. First, to evaluate the present sanitation situation in the fast growing population of Calabar South Nigeria and to design suitable ecological sanitation toilet septic tanks for 8 occupants household and primary school of over 150 students, as an initial awareness of ecological sanitation toilets system in the area. Results from the study showed that less than 40% households have access to good toilet system while about 70% institutions h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…The common practice there is that many tenants are made to share one toilet alongside poor or lack of cleaning routines. This is in agreement with the work of Alepu et al [17] who reported that institutional sanitation rates are very poor in Nigeria.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The common practice there is that many tenants are made to share one toilet alongside poor or lack of cleaning routines. This is in agreement with the work of Alepu et al [17] who reported that institutional sanitation rates are very poor in Nigeria.…”
Section: Discussionsupporting
confidence: 93%
“…The Millennium Development Goal (MDG) targets for sanitation was to reduce by halve the problems by 2015. The country could not meet the MDG's target up till 2016 because most people still lacked access to good water supply which is complimentary to good toilet sanitation in several parts of the country [17][18]. In Calabar South LGA, communal compounds showed high toilet seat contamination 31.6% even after washing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation